2000
DOI: 10.1103/physrevb.62.16116
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic electron emission from clean polycrystalline gold induced by impact of slowC+,N+

Abstract: Ion-induced kinetic electron emission is commonly attributed to collisions of an energetic projectile with quasifree electrons, and to the promotion of atomic levels in binary collisions of the projectile with atomic particles in the solid. The contribution of the promotion processes to the electron emission has been estimated theoretically for all studied systems from molecular-orbital correlation diagrams. As quasifree electron collisional excitations have a sharp threshold at relatively high velocities of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
21
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(30 citation statements)
references
References 16 publications
(18 reference statements)
3
21
0
Order By: Relevance
“…9,10,[17][18][19][20] For our measurements we can rule out the first two mechanisms as the incident energies employed are too low for close-collision-induced promotion and the projectiles are too simple ͑low Z͒ for multielectron effects to arise. Additionally, no Auger transitions analogous to those seen in previous systems exist for our projectiletarget combinations.…”
Section: Rapid Communicationsmentioning
confidence: 99%
See 2 more Smart Citations
“…9,10,[17][18][19][20] For our measurements we can rule out the first two mechanisms as the incident energies employed are too low for close-collision-induced promotion and the projectiles are too simple ͑low Z͒ for multielectron effects to arise. Additionally, no Auger transitions analogous to those seen in previous systems exist for our projectiletarget combinations.…”
Section: Rapid Communicationsmentioning
confidence: 99%
“…10,18,[22][23][24] Nonadiabaticity in this model is included via a time-varying ionsurface interaction that is characterized by the projectile velocity v, the potential V, and a distance-dependent parameter ␥ that accounts for the presence of the surface. 25 Applying this model to our system, we can obtain a probablity of kinetic electron excitation P KEE above the MOS barrier as…”
Section: Rapid Communicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies of secondary electron emission from solid gold targets, however, have found only small secondary electron yields of Շ2 electrons per incident ion 66,67 and mean secondary electron energies of $10 eV (Ref. 68) for a broad range of projectile energies and projectile types.…”
Section: Modeling MMC Energy Spectramentioning
confidence: 99%
“…However, by our experiments, at energies from 1keV to 30 keV, γ for Ga + -ion impact decreases continuously with projectile energy and there is no cut off energy on the low energy side. Since the kinetic energy of the projectile for pKE must be several keV for the promotion of quasi-molecules 23 , it is reasonable to consider that the main process of electron emission for Ga + -ion impact is to be s-KE. For electron emission induced by ions with sub-threshold energies, several papers reported that calculated values of the threshold energies are higher than those of the experiment 29 and practical potential barriers across the surface are lower than the work function 30 .…”
mentioning
confidence: 99%